ES enerģētikas diplomātija: veids, kā orientēties enerģētikas jomā Zaļā darījuma laikmetā - Suri, Maansi (Latvijas Universitāte, 2021)
The European Green Deal encompasses two aspects spanning across the internal-external continuum. Firstly, to achieve climate neutrality, the EU energy sector will undergo a complete transformation and, consequently, play an essential role in the bloc’s transition to a cleaner economy. Secondly, the Green Deal provides the EU with an impeccable opportunity to play a more assertive role in international politics. In this context, energy diplomacy becomes a vital tool for the EU’s objectives. The papers argue that energy diplomacy can help the EU respond to its overall energy situation. In order to answer the research question, first, the EU energy situation has been systematically studied through the SWOT (strengths, weaknesses, opportunities and threats) analysis to outline the action areas that require attention. This has been followed by the Analytical Hierarchical Process (AHP) method and an expert survey to establish critical priorities among the identified SWOT factors, ending with detailed proposals to meet the prioritised energy challenges or opportunities through the energy diplomacy approach. The results of the SWOT-AHP methodology and the expert survey provides the conclusion that the proposal of the EU energy diplomacy should focus upon alleviating the weakness of EU ‘energy dependency’ and work towards meeting the opportunity of ‘first-mover advantage in new cleantech’ and the possible threat of ‘inadequate global climate action’.Along with this, it should also take the help of the EU’s leadership in the renewable sector within its strategic plan. Therefore, the research proposal is based on establishing a green hydrogen partnership between the EU and North Africa. Green hydrogen imports from North Africa will contribute to EU energy security and help it realise its renewable export potential.
EU Energy Diplomacy: a way to navigate energy interests inthe Green Deal era
Keywords: Ekonomika; Energy diplomacy; EU energy diplomacy; European Green Deal; Green hydrogen; North Africa